Occupational accidents in healthcare workers: a bibliometric analysis in Scopus database 2010-2019 - Vera Ponce, Víctor Juan (2022)
| Scientific publications in the occupational area have a growing trend towards management of safety in the workplace, despite lack of knowledge on the distribution and characteristics of scientific evidence on occupational accidents in healthcare professionals. This study aims to determine the characteristics and collaboration networks of publications, the co-occurrence of terms, and the main journals on occupational accidents in healthcare professionals among publications indexed in Scopus from 2010 to 2019. This is an observational, cross-sectional, bibliometric study based on publications indexed in the Scopus database. The indicators were number of publications per year, main journals of publication and its quality index, collaboration networks between authors, and co-occurrence of terms. The predominant language of publication was English, the main type of study was the observational one, and nursing professionals represent the main group of interest (31.14% of the articles), contrary to radiologists and/or physical therapists (4% each). The main source of publication about occupational accidents was Workplace Health and Safety, and the main themes of investigation were related to puncture injuries and infection by hepatitis B and C. There is a growing trend towards research on occupational accidents of independent authorship, despite the creation of collaboration networks in the last years. Furthermore, nurses and surgeons are the target group of greatest interest, and the main topics cover infectious diseases.